A multichannel pipeline analog-to-digital converter for an integrated 3-D ultrasound imaging system. - Kaviani, K. (IEEE Journal of solid state circuits)
An 8-channel 10-bit pipeline analog-to-digital converter, designed for use in an integrated three-dimensional ultrasound imaging system, has been implemented in a 0.25-μm CMOS technology. Two parallel multiplexing sample-and-hold stages are employed to multiplex a total of eight adjacent ultrasound channels, each sampled at 20 MHz. The sampled and multiplexed signals are fed into two parallel time-interleaved pipeline paths, each operating at 80 MHz. The two parallel pipelines are subsequently multiplexed into a single pipeline operating at 160 MHz to conserve area and reduce complexity. An experimental prototype of the proposed architecture occupies less than 4 mm2 of active silicon area and shows a peak signal-to-noise-plus-distortion ratio more than 54 dB for a 2.1-MHz input signal, while dissipating only 20 mW of analog power per input channel from a 2.5-V supply.